Cluster Preface: Catalytic Aerobic Oxidations - Stahl, Shannon S.; Rovis, Tomislav (Synlett, 2017)
Shannon S. Stahl was an undergraduate at the University of Illinois at Urbana-Champaign, and a graduate student at Caltech (PhD, 1997), where he worked with Professor John Bercaw. He was an NSF postdoctoral fellow with Professor Stephen Lippard at Massachusetts Institute of Technology from 1997–1999. He is currently a Professor of Chemistry at the University of Wisconsin–Madison, where he began his independent career in 1999. His research group specializes in catalysis, with an emphasis on aerobic oxidation reactions and oxygen chemistry related to energy conversion.Tomislav Rovis was born in Zagreb in former Yugoslavia but was largely raised in southern Ontario, Canada. He earned his PhD degree at the University of Toronto (Canada) in 1998 under the direction of Professor Mark Lautens. From 1998–2000, he was an NSERC Postdoctoral Fellow at Harvard University (USA) with Professor David A. Evans. In 2000, he began his independent career at Colorado State University and was promoted in 2005 to Associate Professor and in 2008 to Professor. His group’s accomplishments have been recognized by a number of awards including an Arthur C. Cope Scholar, an NSF CAREER Award, a Fellow of the American Association for the Advancement of Science and a Katritzky Young Investigator in Heterocyclic Chemistry. In 2016, he moved to Columbia University where he is currently Professor of Chemistry.